Small global effect on terrestrial net primary production due to increased fossil fuel aerosol emissions from East Asia since the turn of the century. Issue 15 (14th August 2016) - O'Sullivan, M.; Rap, A.; Reddington, C. L.; Spracklen, D. V.; Gloor, M.; Buermann, W.
Abstract: The global terrestrial carbon sink has increased since the start of this century at a time of growing carbon emissions from fossil fuel burning. Here we test the hypothesis that increases in atmospheric aerosols from fossil fuel burning enhanced the diffuse light fraction and the efficiency of plant carbon uptake. Using a combination of models, we estimate that at global scale changes in light regimes from fossil fuel aerosol emissions had only a small negative effect on the increase in terrestrial net primary production over the period 1998–2010. Hereby, the substantial increases in fossil fuel aerosol emissions and plant carbon uptake over East Asia were effectively canceled by opposing trends across Europe and North America. This suggests that if the recent increase in the land carbon sink would be causally linked to fossil fuel emissions, it is unlikely via the effect of aerosols but due to other factors such as nitrogen deposition or nitrogen‐carbon interactions. Key Points: Increase in FF aerosol emission over East Asia contributes substantially to regional increase in plant carbon uptake The global impact is small since increases in FF aerosols and NPP in East Asia were canceled by opposing trends in Europe and North America Thus, the increase in FF aerosols over East Asia may not act as a mechanism that would explain coincident increase in land carbon sink